Production of Talk Show Program â€œBreakoutâ€ and â€œKimchiâ€ at PRO 2 RRI Semarang (Creative Director) - Margaret, Liza; Ratri Rahmiaji, M.Si, Dr. Lintang (Interaksi Online, 2016)
The Radio of Republic Indonesia (Radio Republik Indonesia - RRI) is the oldest and the only governmentâ€™s radio which has visions to embody Indonesia public broadcasting as the extensive network radio, character development of nation, and as the world class radio. RRI has a very extensive network, from Aceh to Papua, but not many young people are interested listening to the RRI. The basic reasons of that case are the RRI image as radio news and radio for the older. Solution to overcome the matter is creating talk show programs like â€œBreakoutâ€ and â€œKimchiâ€ in PRO 2 RRI Semarang. Those programs are addressed to young people as the listener target. Thus, the paramount expectation by creating those programs is to increase the listener of RRI PRO 2 Semarang, in particular the young people. During the execution of those programs, the author acts as creative director who has the responsibility to make the programs more interesting by making earcatcher, voxpop, quiz and poster in supporting the process of buzzing in media social. Result of the post-production questionnaire shows that through the production of "Breakout" and "Kimchi" talk show, we succeed to increase the number of PRO 2 RRI listeners. At first the program "Kimchi" was only 8% of the initial data we collect but then increased to 67%. While the program "Breakout" which was initially 28%, then increased to 65%. Another finding is the program "Kimchi" increased more than in the "Breakout". In addition, culinary theme is the theme that most interests the listener. It is proven from the success of both talk show program that resulted from the combination of right buzzing, interesting material such as voxpop and earcatcher, good cooperation between broadcasters and sources, and a quiz with prizes.